2018
DOI: 10.1097/ijg.0000000000000919
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation Syndrome: A Disease of Autophagy and LOXL1 Proteopathy

Abstract: Exfoliation syndrome (XFS) is an age-related disease involving the deposition of aggregated fibrillar material (exfoliation material) at extracellular matrices in tissues that synthesize elastic fibers. Its main morbidity is in the eye, where exfoliation material accumulations form on the surface of the ciliary body, iris, and lens. Exfoliation glaucoma (XFG) occurs in a high proportion of persons with XFS and can be a rapidly progressing disease. Worldwide, XFG accounts for about 25% of open-angle glaucoma ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
11
1
Order By: Relevance
“…Although the autophagy gene set was not enriched in the current study ( P = 0.79), several autophagy genes were differentially expressed, providing further suggestion that disordered autophagy may be relevant to PEX. 58 By contrast, we did not observe expression changes in extracellular matrix genes including LTBP1 , LTBP2 , TIMP1 , and TIMP2 , which have been demonstrated to exhibit differential expression in PEX tissues. 27 , 28 , 35 Reasons for differences between these results and the current data are unclear.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Although the autophagy gene set was not enriched in the current study ( P = 0.79), several autophagy genes were differentially expressed, providing further suggestion that disordered autophagy may be relevant to PEX. 58 By contrast, we did not observe expression changes in extracellular matrix genes including LTBP1 , LTBP2 , TIMP1 , and TIMP2 , which have been demonstrated to exhibit differential expression in PEX tissues. 27 , 28 , 35 Reasons for differences between these results and the current data are unclear.…”
Section: Discussioncontrasting
confidence: 83%
“…In parallel to genetic investigations of PEX which have identified multiple disease-associated risk loci, 10 19 biological studies have demonstrated that perturbations in physiological processes including oxidative phosphorylation, 56 , 57 autophagic flux, 51 , 58 and the unfolded protein response 47 may contribute to the PEX disease process. Furthermore, latitudinal differences in PEX prevalence have led to hypotheses that environmental exposures, such as ultraviolet light, may contribute to the disease.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the findings of this study provided evidence of a link between PEX-associated fibrosis and impaired RA signaling in ocular tissues which may be influenced by genetic and environmental factors. Dysregulated RA signaling has the potential to contribute to PEX pathogenesis through multiple downstream pathways which are known to be involved in PEX pathogenesis, including TGF-β1 and Wnt signaling pathways, autophagy, and mitochondrial dysfunction [ 3 , 56 ]. The interaction of the RA signaling pathway with all these pathways is well documented [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Over time, the XFM pileup appears to nibble away at the endothelial cells that line blood vessels, as well as the pericytes, contractile cells that wrap around the endothelial cells and help give blood vessel walls strength and flexibility; these cellular changes may impact vascular tissue around the body. XFS may also be associated with compromised autophagy of cellular waste, and this may lead to buildup of misfolded proteins 56. This abnormality may result in oxidative stress leading to vascular pathology.…”
Section: Discussionmentioning
confidence: 99%